Pengaruh Metode Sosiodrama terhadap Motivasi Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam MI Al-Hidayah Ciampea Bogor - Muhamad Budi; Ahmad Waki; M. Zainal Arifin (Prodi PGMI IAI Sahid, 2022)
The problem examined in this study is to determine whether there is an influence between the use of sociodrama methods on student motivation, especially on SKI lessons. And to find out how much influence between the use of sociodrama methods on student motivation in MI Al-Hidayah Ciampea Bogor. This research is a descriptive correlation study. To conduct this research, a quantitative research approach was used. The sample in this study were all fifth grade students, totaling 23 students. In collecting data used questionnaire and observation techniques. Data analysis used was correlational analysis using the